Visualisation and reconstruction in dentistry - Shimabukuro, Milton H. [UNESP]; Minghim, Rosane [UNESP]; Licciardi, Paulo Renato D B [UNESP] (IEEE Computer Soc, 1998)
Visualisation in the field of dentistry has nor, thus far, reached the same development as other medical fields. Potential applications of visualisation techniques in this area, however, are many, ranging from educational displays to training for delicate procedures. This paper reports on the investigation of techniques for handling three-dimensional models of teeth, aiming at investigation of dental structures. An algorithm was implemented for this purpose, which reconstructs three-dimensional teeth models from two-dimensional contour slices. Results employing various data sets are presented, including the output of VRML models for exploration.
Keywords: Algorithms; Computational geometry; Computer simulation languages; Dentistry; Image reconstruction; Virtual reality; Visualization; Three dimensional teeth models; Virtual reality modeling language (VRML); Three dimensional computer graphics